2021
DOI: 10.3389/fnagi.2020.613628
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroimmunology of Guillain-Barré Syndrome and the Potential Role of an Aging Immune System

Abstract: Guillain-Barré syndrome (GBS) is a paralyzing autoimmune condition affecting the peripheral nervous system (PNS). Within GBS there are several variants affecting different aspects of the peripheral nerve. In general, there appears to be a role for T cells, macrophages, B cells, and complement in initiating and perpetuating attacks on gangliosides of Schwann cells and axons. Of note, GBS has an increased prevalence and severity with increasing age. In addition, there are alterations in immune cell functioning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 177 publications
(237 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, Yoshii and Shinohara discovered that natural killer cell function was lower in GBS than in the control group [ 4 ]; the authors suggested that natural killer cell activity deficiencies could leave people vulnerable to GBS because these cells suppress the immune system [ 4 ]. The majority of GBS studies, on the other hand, have concentrated on the diagnostic and prognostic role of cytokines [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, Yoshii and Shinohara discovered that natural killer cell function was lower in GBS than in the control group [ 4 ]; the authors suggested that natural killer cell activity deficiencies could leave people vulnerable to GBS because these cells suppress the immune system [ 4 ]. The majority of GBS studies, on the other hand, have concentrated on the diagnostic and prognostic role of cytokines [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of GBS studies, on the other hand, have concentrated on the diagnostic and prognostic role of cytokines [ 30 ]. Not surprisingly, because of the robust immune response, there are changes in cytokine and inflammatory biomarkers' levels in GBS [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations